2017
DOI: 10.1080/23729333.2017.1300996
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into challenges experienced when route planning, navigating and wayfinding

Abstract: Some map users still experience difficulties when attempting to route plan, navigate and/or wayfind. This paper provides information on the outcomes of a research project that aims to identify the nature of the difficulties/challenges these users experience. The paper draws on findings from studies of strategies used by novice and experienced map users, and users with poor spatial abilities, to identify the skills that those with poor spatial abilities or with little map reading experience lack. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
(11 reference statements)
0
12
0
Order By: Relevance
“…The apps being developed based on VGI have become widely distributed. For example, the "Maps.me" [20,21] app based on VGI by OSM has been adopted by more than 100 million users [21].…”
Section: Introductionmentioning
confidence: 99%
“…The apps being developed based on VGI have become widely distributed. For example, the "Maps.me" [20,21] app based on VGI by OSM has been adopted by more than 100 million users [21].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers investigating human-centred navigation [5] have looked for ways to redesign cartographical representations to improve the efficiency and effectiveness of wayfinding for users with spatial cognitive difficulties. However, the focus of these studies was outdoor wayfinding [6,7] and an exploratory study on how users accomplish their wayfinding behaviors in indoor environments is a challenging endeavour.…”
Section: Introductionmentioning
confidence: 99%
“…In the past several decades, mobile (head-worn) eye tracking has become a popular research method that has found widespread use across a range of fields. The opportunity afforded by head-worn eye-tracking setups to acquire data on the visual behavior of participants who freely move around has enabled researchers to conduct studies in fields such as vision science (Land, 1992;Land & Lee, 1994;Ballard et al, 1995;Pelz & Canosa, 2001;Matthis et al, 2018), social interaction between adults (Ho et al, 2015;Rogers et al, 2018;Macdonald & Tatler, 2018;Rogers et al, 2019) or children and their parents (Yu & Smith, 2017;Suarez-Rivera et al, 2019), usability (Masood & Thigambaram, 2015;Bergstrom & Schall, 2014), marketing (Harwood & Jones, 2014), decision making (Gidlöf et al, 2013;Gidlöf et al, 2017), surgery (Dik et al, 2016;Harrison et al, 2016), navigation and wayfinding (Kiefer et al, 2014;Koletsis et al, 2017) and education (McIntyre et al, 2017;McIntyre & Foulsham, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Tobii Pro Glasses 2 is a recent head-worn eye tracker that is commonly used across a range of studies (e.g., Harrison et al, 2016;Topolšek et al, 2016;Koletsis et al, 2017;Rogers et al, 2018;Raptis et al, 2018). However, analysis of the recordings is currently limited to Tobii Pro Lab, a software package sold by the manufacturer of this eye tracker, and other closed commercial software packages such as offered by iMotions.…”
Section: Introductionmentioning
confidence: 99%